Beyond the Façade: Haussmannization in Paris as a Transformation of Society - Amy Rideout (Pursuit - The Journal of Undergraduate Research at the University of Tennessee, 2016)
The Paris that tourists know and love today conceals under its romantic, ordered, urban environment a façade of division and social change. Following Napoleon II’s commissioning of an urban overhaul, Haussmannization in the nineteenth century addressed problems of circulation and disorder, but also created problems of separation and division. Annexing several neighborhoods into a fortified new boundary, and subsequently removing the poor, working class to the outskirts, helped make this division permanent. While modern concepts and building materials significantly improved the inner city, they also forced a reduction in housing supply coupled with increased housing prices. Slums were cleared, in part because of the view that the poor were morally inferior to the wealthy. Also aiding in increasing the wealth of a certain class was the rise of capitalism and consumerism. New arcades and galéries lured shoppers into lives of consumerism and, to the conservative Catholic leaders, a life of sinful ostentation. Writers like Baudelaire integrated their private lives into a new public urbanism, while trends in apartment layout revealed tensions between rich and poor, public and private. Social tensions boiled over in conflicts like the Bloody Week of 1871, and monuments like Sacré Coeur were built with and incurred changing social symbolism. In sum, Haussmannization created, for better or worse, the Paris that we know today.